Identifikasi Miskonsepsi Siswa pada Materi Gaya dan Gerak Menggunakan Certainty of Respons Index (CRI) di Sekolah Dasar - Arruum, Naziroh Lembar; Desstya, Anatri (Jayapangus Press, 2024)
Elementary school students must understand all concepts in science materials, but there are indications that student understanding still needs to be improved, and misconceptions appear. This study aims to identify fifth-grade elementary school students' understanding of force and motion material using the Certainty of Response Index (CRI) method. This research is qualitative and is located at Bangunsari Pacitan Elementary School. The data collection technique used was a CRI-based written test. The test instrument used is in the form of multiple choice questions accompanied by the CRI confidence level, which has been previously tested with a validity value of 0.444-0.661 and a reliability of 0.699. The results showed that students with conceptual understanding amounted to 34.92%, did not understand the concept of 16.51%, and misconceptions reached 48.57%. The highest misconception is in magnetic force material, with a misconception percentage of 100%, while the lowest misconception is in the definition of motion, with a misconception percentage of 9.52%.